O-029 The Importance of Core Infarct Volume in the Number Needed to Treat in Endovascular Therapy for Acute Ischemic Stroke. (26th July 2014) - Zaidat, O; Yoo, A; Janardhan, V; Frei, D; Ammar, L; Meyer, D; To, C; Kuo, S; Buell, H; Barraza, L; Bose, A; Sit, S
Abstract : Introduction/purpose: The infarct core has been theorised to be an important indicator for treatment success from endovascular intervention in acute ischemic stroke from large vessel proximal occlusion. The objective of this study was to determine the extent to which it contributes to the number of patients needed to treat (NNT) to achieve long-term functional independence. Materials and methods: Patients treated by the Penumbra System with acute stroke not eligible and/or refractory to IV rtPA were pooled from numerous trials (N = 463): Pivotal (N = 83), PICS (N = 174), RetroSTART (N = 96) and START (N = 110) and compared to a control group of 82 patients who were eligible for but not treated by endovascular therapy. The NNT for both groups to achieve an mRS score of ≤2, the indicator for 90-day functional independence, were compared. The effects of the infarct core at baseline described by ASPECTS trichotomised as small (10–8), medium (7–5) and large (4–0) were evaluated. The distribution of the infarct core (N) for Penumbra:Control patients were 257:65, 155:8 and 51:4, respectively, for small, medium, and large. Five control patients did not have ASPECTS scores. Results: The baseline characteristics between the two groups' median values (Penumbra:Control) were similar: Age (68:71), NIHSS (17:20), ASPECTS (ASP) (8:9). Post-treatment rate of revascularization, all-cause mortality and good functional outcome (mRS <2) were significantly different, but not symptomatic ICH rate (Table 1 ). The NNT to achieve independent functional status was 4.8 for the entire cohort of treated patients and for those with small, medium, or large core infarcts were 4.1, 3.7, and 12.8, respectively. Conclusion: The data confirmed that endovascular therapy may not be as successful in patients with a large infarct core, leading to a high NNT to achieve long-term functional independence. Excluding this group at time of triage may effectively lower the NNT and improve the response rate of this therapy. Disclosures: O. Zaidat: 1; C; Penumbra Inc. 3; C; Penumbra Inc. A. Yoo: 1; C; National Institutes of Health, Penumbra Inc., Remedy Pharmaceuticals. V. Janardhan: None. D. Frei: 3; C; Penumbra Inc. 4; C; Penumbra Inc. L. Ammar: 5; C; Penumbra Inc. D. Meyer: 5; C; Penumbra Inc. C. To: 5; C; Penumbra Inc. S. Kuo: 5; C; Penumbra Inc. H. Buell: 5; C; Penumbra Inc. L. Barraza: 5; C; Penumbra Inc. A. Bose: 4; C; Penumbra Inc. 5; C; Penumbra Inc. S. Sit: 4; C; Penumbra Inc. 5; C; Penumbra Inc.